Lazarus man - Price, Richard 1949- (Farrar, Straus and Giroux, 2024)
"East Harlem, 2008. In an instant, a five-story tenement collapses into a fuming hill of rubble ... As the city's rescue services and media outlets respond, the surrounding neighborhood descends into chaos. By day's end, six bodies have been recovered but many of the other tenants are missing. In Lazarus Man, Richard Price ... creates intertwining portraits of a group of compelling and singular characters whose lives are permanently affected by the disaster."
Keywords: Building failures / Fiction; Tenement houses / Fiction; Life change events / Fiction; Harlem (New York, N.Y.) / Fiction; New York (N.Y.) / Fiction; Building failures; Life change events; Tenement houses; New York (State) / New York; New York (State) / New York / Harlem; Novels